Geochemistry and geochronology of granitoid rocks of the Taatsiin Gol pluton of the Khangai Complex, Central Mongolia - Bayasgalan, Tsogoo; Munkhtsengel, Baatar; Khishigsuren, Sodnom; Khurelbaatar, Battur (Mongolian Geoscientist, 2021)
The Taatsiin Gol pluton is one of the major constitute the intrusive body of the Khangai Complex, and is composed the first phase of diorite, the second phase of porphyritic granite, biotite-hornblende granite, and granodiorite, and the third phase of biotite granite and alkali granite. This paper presents new geochemical and U-Pb zircon age data from intrusive rocks of the Taatsiin Gol pluton. Geochemical analyses show that the granitoid rocks of the pluton are high-K calc-alkaline, and metaluminous to weakly peraluminous I-type granites, depleted in HFSE such as Nb, Ta, Ti and Y and enriched in LILE such as Rb, Cs, Th, K and LREE, where some variations from early to later phases rock. Zircon U-Pb dating on the biotite granite of the third phase yielded weighted mean ages of 241.4±1.2 Ma and 236.7±1.4 Ma. Based on the new and previous researchers’ age results, the age of the Taatsiin Gol pluton of the Khangai Complex is 256-230 Ma consistent with the late Permian to mid-Triassic time. Although showing variated geochemical features, the rocks of the three phases are all suggested to form at an active continental margin setting, probably related to the southwestward subduction of the Mongol-Okhotsk Ocean plate during the late Permian to mid-Triassic period.